Management of Majelis Taklim Contact Agency in Improving Literacy Religious Moderation of Mothers of Majelis Taklim Members in Medan City - Yanti Panggabean, Juwita; Zainun, Zainun (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The Contact Body of the Taklim Assembly is a state power, every village has a gem, every region or sub-district has a BKMT, every district has a BKMT, every country has a BKMT area, there is a leader. This institution carries out its activities in an organized and structured manner so that it becomes a pillar in maintaining religious moderation. This research discusses the management of BKMT in improving the literacy of religious moderation of mothers and members of the Ta’lim assembly, the program at BKMT was also analyzed in the context of BKMT management, in this study, the focus is given on how to study, the literacy of religious moderation among mothers, mothers members of the Ta’lim assembly. This research uses a qualitative approach with data collection through interviews and observations related to BKMT and religious moderation literacy the data collected will be analyzed to identify an increase in religious moderation literacy among BKMT mothers of the BKMT program program in increasing religious moderation literacy. The purpose of this research is to provide insight, especially about BKMT management in improving the literacy of religious moderation among mothers and mothers of BKMT members as well as providing insight about the program programs implemented by BKMT in increasing religious moderation. As for the results of the research that I got, one of the religious moderation programs in BKMT is by sacrificing every year visiting minority areas, and distributing the sacrifice to non-Muslims in that area. The next, obstacle in the implementation of the religious moderation program is the lack of self-awareness of the tolerance of the mothers of BKMT members because there is still a lack of self-understanding about the importance of religious moderation, then willing to listen to the explanation of religious moderation among the BKMT and the lack of support from the surrounding environment about the way of tolerance and the strategy carried out by the BKMT in responding to the problem is with the deliberation against the mothers of BKMT members, it is hoped that they can apply religious moderation in the community so that the program can be carried out properly.